Cosmic reionization in a dynamic quintessence cosmology - Crociani, Daniela; Bartelmann, Matthias (Arxiv, 2017)
In this paper we investigate the effects that a dynamic dark energy component dominant in the universe at late epochs has on reionization. We follow the evolution of HII regions with the analytic approach of Furlanetto and Oh (2005) in two different universes for which we assume the Peebles and Ratra (2003) and Brax and Martin (2000) quintessence models and we compare our results to the LCDM scenario. We show that, for a fixed ionization efficiency, at the same cosmological epoch the topology of bubbles is dominated by high-mass objects and the characteristic size of the ionized regions is slightly smaller than in the LCDM model, especially at the latest stages of reionization, due to the higher recombination efficiency. As a consequence, the bubbles' `epoch of overlap' happens earlier than in LCDM. Finally, we show how the different evolution of the HII regions affects the transmission of the high-z QSO spectra, reducing the Lyman flux absorption at small optical depths.
Gesehen am 25.09.2017